Biznesy rodzinne źródłem bogactwa narodów? : wnioski z badań empirycznych family business w Polsce - Sułkowski, Łukasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The issue of family business has become more and more significant in the last decade, both in the theory and practice of management sciences. The article presents conclusions from the research on characteristics of family business management in Poland. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 504-518